The Conventional And Conversational Implicature In The Film Enola Holmes : A Pragmatic Analysis - Niken Niken; Amelia Yuli Astuti Amelia Yuli Astuti (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research aims to analyze the types of implicature contained in the Enola Holmes film, as well as explain the meaning contained in it based on Grice's theory of implicature. This research uses descriptive qualitative approach with documentation method. The data were collected from the dialogues between characters in Enola Holmes movie that contain implied meanings, and analyzed based on the theory of implicature which includes conventional implicature and conversational implicature. The results showed that out of 36 data collected, 12 data were categorized as conventional implicature. Meanwhile, the other 24 data are conversational implicatures, consisting of 4 General Conversational Implicature (GCI ) data and 20 Particular Conversational Implicature (PCI)  data. Conventional implicature in this film is characterized by the use of certain expressions that have additional meanings without requiring extensive context. In contrast, conversational implicature arises from the violation of Grice's maxims of cooperation, such as the maxims of quantity, quality, relevance, and manner. These findings suggest that implicature is used effectively to strengthen communication in movies, both in message delivery and character development.